Design and Schematic Evaluation of Dextran Conjugated Dexibuprofen, a Gastrosparing NSAID - P, Jaya Preethi; A, Lakshmana Rao; MV, Basaveswara Rao (American Journal of Chemistry, 2018)
A novel prodrug approach was undertaken to develop the safe and therapeutically efficacious dexibuprofen to avoid oral NSAIDs induced ulceration. Dexibuprofen was esterified with dextran, using N,N-carbonyldiimidazole in one pot reaction. Synthesized dexibuprofen prodrug was characterized and evaluated by FT-IR and NMR spectroscopy, molecular weight, lipophilicity, partition coefficient, protein binding, degree of substitution, hydrolysis in simulated GI fluids, in-silico ADME properties and pharmacological potentials. Structural profile of dexibuprofen prodrug was elucidated by an ester linkage, glucosidic ring anomeric proton, dextran monomer protons and ester carbonyl carbon signals. Prodrug possessed physicochemical features as molecular weight of 83,368.11 g/mol, log P of 5.4 with optimal protein binding of 66% and degree of substitution of 25.3%. It was significantly hydrolyzed in SIF (99.53%) by following first-order kinetics with 85.9 min half-life. In-silico ADME properties of prodrug satisfied the Lipinski' rule of five and Jorgensen's rule of three without any CNS activity and cardiac toxicity, thus prodrug was suitable for oral administration. Prodrug has exhibited superior analgesic, anti-inflammatory, antipyretic activities devoid of antigenecity and ulceration in experimental animals. Data of the study were thus evinced that dexibuprofen prodrug is a safer therapeutic moiety in effective management of acute inflammation, pain and fever.